African progress and colonial modernity as seen through the Zulu pages of the Bantu world, 1932-1952 - Sifelani, Portia (My University, 2018)
This study explores the Zulu pages of the Bantu World from 1932 to 1952. It focuses on how the Zulu-language contributors, in their letters and articles, engaged with the idea of the role that people of European descent had to play in the achievement of progress by Africans. This was mainly inspired by the fact that many Zulu articles that commented on the need for Africans to progress from a state of poverty and oppression, made constant comparisons between Africans and Europeans. There was a tendency to refer to the qualities of white people which had ensured that they achieved economic and political dominance, a feat which black people were yet to realise. An analysis of the discussions around this question reveals that the Zulu pages were a platform used by the Zulu-language writers to express ideas which were otherwise not expressed fully in English due to censorship and their preference of the Zulu language. I begin in chapter one by providing a historical background to the Bantu World by showing how the African languages press emerged from the late nineteenth to the twentieth centuries. This chapter also discusses the origins of the Bantu World and its intended purpose. Chapter two focuses on the ideological context which influenced the editors and the contributors of the Bantu World. I argue that it was the influence of Booker. T Washington on Selope Thema which predominantly became manifest in the paper and determined the themes that were discussed. In chapters three and four I then analyse some of the issues that were discussed in the Zulu pages of the Bantu World and these included the problem of disunity, perceptions about white people in relation to progress, self-help and entrepreneurship as well as the brief removal and return of the Zulu pages. The debates regarding these issues were to a large extent rooted in efforts to map a way forward as far as achieving progress was concerned. They also reflect a constant ambivalence with regards to the perceptions of the Zulu-language writers on the role that white people had to play in the achievement of this progress.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Arts in History by Research Report to the Faculty of Humanities, University of the Witwatersrand , 2018
Keywords: Zulu language--Grammar; Literacy--Social aspects